The effect of peers support on fear of hypoglycemia in iranian patients with type 1 diabetes: A clinical trial study - Leila Dehghankar; Peyman Namdar; Leili Yekefallah; Narges Hosseini; Mahnaz Moradi (Wolters Kluwer Medknow Publications, 2021)
Background: Fear of hypoglycemia is a medical emergency which leads to disrupt individuals' normal lives. Peers support is a hopeful approach to improve diabetes self-care behaviors. This study was conducted to assess the effect of peers support on the fear of hypoglycemia in patients with type 1 diabetes. Materials and Methods: This randomized clinical trial study was performed among 60 patients with type 1 diabetes in Qazvin city from September 2019 to October 2020. Patients were assigned to control and intervention groups using a random method. The data collection tools included demographic characteristics and a standard questionnaire for Hypoglycemia Fear Survey (HFS). Patients in the intervention group were trained by skilled peers for 2 months, but those of the control group only received routine hospital training. The data were analyzed by SPSS version 16 and paired and independent t-test. Results: The scores of the fear of hypoglycemia in diabetic patients in the two groups had no significant statistical difference before intervention (t53 = 0.93, p = 0.94). But after the intervention, the independent t-test showed that there was a significant difference between the scores of the fear of hypoglycemia in both groups (t53 = -2.13, p = 0.03). Conclusions: Considering the results of the current study, peer support for diabetic patients is an effective way to reduce the fear of hypoglycemia. Therefore, it is recommended using this training method to train diabetic patients.